Penatalaksanaan dan Pencegahan Penyakit Pedikulosis Kapitis pada Anak Panti Asuhan: Management and Prevention of Pediculosis Capitis in Orphanage Children - Maryanti, Esy; Wardany, Yulia; Namira, Syafira Nihla; Putratama, Muhammad Hafiz; Mislindawati, Mislindawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Pediculosis capitis is a common parasitic infestation in humans and often affects children. This disease is caused by head lice, Pediculus humanus var. capitis, an ectoparasite that infests the scalp and hair with the main symptoms being itching and irritation of the scalp. Generally, children who are infested with head lice do not show serious symptoms, but in some children, it can cause problems in the form of sleep disturbances and loss of concentration when studying and this will disrupt the child's growth and development. An orphanage is a place to live with a group of children who are at risk of head lice infestation. This community service activity aims to carry out head and hair examinations, provide management for children who are positively infested with head lice, and provide education for eradicating and preventing this disease to orphanage residents. This activity was successfully carried out at the Air Jamban Village Orphanage, and the incidence of pediculosis capitis was found to be 30.7%. Children who are infested with head lice are given pharmacotherapy treatment in the form of 1% permethrin lotion and non-pharmacotherapy in the form of a wet comb. To prevent this disease, education was carried out in the form of counseling and an increase in the knowledge of the orphanage residents was obtained before and after the education. It is hoped that this activity can improve the health status of orphanage residents.